Hyperexcitability of Rat Thalamocortical Networks after Exposure to General Anesthesia during Brain Development - DiGruccio, Michael R. (J Neurosci, 2015)
Prevailing literature supports the idea that common general anesthetics (GAs) cause long-term cognitive changes and neurodegeneration in the developing mammalian brain, especially in the thalamus. However, the possible role of GAs in modifying ion channels that control neuronal excitability has not been taken into consideration. Here we show that rats exposed to GAs at postnatal day 7 display a lasting reduction in inhibitory synaptic transmission, an increase in excitatory synaptic transmission, and concomitant increase in the amplitude of T-type calcium currents (T-currents) in neurons of the nucleus reticularis thalami (nRT). Collectively, this plasticity of ionic currents leads to increased action potential firing in vitro and increased strength of pharmacologically induced spike and wave discharges in vivo. Selective blockade of T-currents reversed neuronal hyperexcitability in vitro and in vivo. We conclude that drugs that regulate thalamic excitability may improve the safety of GAs used during early brain development.